2017
DOI: 10.5301/jva.5000658
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine-impregnated transparent dressings decrease catheter-related infections in hemodialysis patients: a quality improvement project

Abstract: Replacing adhesive dry gauze dressing with CHG-transparent dressing for hemodialysis patients with tunneled CVC was associated with decreased CRI rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
0
15
0
4
Order By: Relevance
“…16,17 There are two published studies in which chlorhexidine-based exit site applications were performed in patients using TCs for hemodialysis, however their the outcomes are conflicting. 18,19 The first study compared a chlorhexidine-impregnated sponge dressing vs. a transparent dressing (dressings were changed weekly in both groups), and found no difference in CRBSI in a small cross-over study. 18 In contrast, a significant reduction in CRBSI was reported in a recent quality improvement project using chlorhexidine transparent dressings (changed weekly) vs. dry gauze dressings and antibiotic ointment (changed thrice weekly).…”
Section: Catheter Exit Site Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 There are two published studies in which chlorhexidine-based exit site applications were performed in patients using TCs for hemodialysis, however their the outcomes are conflicting. 18,19 The first study compared a chlorhexidine-impregnated sponge dressing vs. a transparent dressing (dressings were changed weekly in both groups), and found no difference in CRBSI in a small cross-over study. 18 In contrast, a significant reduction in CRBSI was reported in a recent quality improvement project using chlorhexidine transparent dressings (changed weekly) vs. dry gauze dressings and antibiotic ointment (changed thrice weekly).…”
Section: Catheter Exit Site Applicationmentioning
confidence: 99%
“…18 In contrast, a significant reduction in CRBSI was reported in a recent quality improvement project using chlorhexidine transparent dressings (changed weekly) vs. dry gauze dressings and antibiotic ointment (changed thrice weekly). 19 A well-powered, and well-designed study is needed to evaluate chlorhexidinebased exit site applications for use in hemodialysis TCs.…”
Section: Catheter Exit Site Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Es gibt Produkte, bei denen der Exit mit einem Gelkissen abgedeckt wird, das Chlorhexidin freisetzt. Für diese Produkte ist sowohl in der Intensivmedizin als auch in der Dialyse nachgewiesen worden, dass sie die Rate an BSI reduzieren können[7]. Auch diese Produkte kommen daher als valide Maßnahme infrage, wenn die BSI-Rate in einem Zentrum auffällig hoch liegt.…”
unclassified
“…The use of a combination of CAI prophylaxis measures in a standardized protocol has been shown to reduce rates of CAB . However, while multiple trials and meta‐analyses have demonstrated benefit for individual products or procedures the optimal combination of prophylactic measures remains unknown. In this context, significant clinical variability in catheter management practices across Australia and New Zealand dialysis units might be expected.…”
mentioning
confidence: 99%